Multimodal Magnetic Nanoclusters for Gene Delivery, Directed Migration, and Tracking of Stem Cells. (29th May 2017) - Park, Ji Sun; Park, Wooram; Park, Sin‐jung; Larson, Andrew C.; Kim, Dong‐Hyun; Park, Keun‐Hong
Abstract : This study develops multimodal magnetic nanoclusters (M‐MNCs) for gene transfer, directed migration, and tracking of human mesenchymal stem cells (hMSCs). The M‐MNCs are designed with 5 nm iron oxide nanoparticles and a fluorescent dye (i.e., Rhodamine B) in the matrix of the Food and Drug Administration approved polymer poly(lactide‐ co ‐glycolide) using a nanoemulsion method. The synthesized M‐MNCs have a hydrodynamic diameter of ≈150 nm, are internalized by stem cells via endocytosis, and deliver genes with high efficiency. The cellular internalization and gene expression efficiency of the clustered nanoparticles are significantly higher than that of single nanoparticles. The M‐MNC‐labeled hMSCs migrate upon application of a magnetic force and can be visualized by both optical and magnetic resonance (MR) imaging. In animal models, the M‐MNC‐labeled hMSCs are also successfully tracked using optical and MR imaging. Thus, the M‐MNCs not only allow the efficient delivery of genes to stem cells but also the tracking of cells in animal models. Taken together, the results show that this new type of nanocomposite can be of great help in future stem cell research and in the development of cell‐based therapeutic agents. Abstract : Multimodal magnetic nanoclusters (M‐MNCs) for gene delivery, directed migration, and tracking of stem cells are developed through an easy nanoemulsion method. The M‐MNCs show high transfection efficacy and allow directed migration of the stem cells under magnetic fields and provide multimodal imaging modality to enable tracking of the stem cells.